การตอบสนองของลูกค้าในอำเภอเมืองเชียงใหม่ต่อสิทธิประโยชน์ของสมาชิกบัตรเครดิตเคทีซีไทเทเนียม - กฤติยา ไฉนงุ้น (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
This independent study aimed to explore the responses of customers in Mueang Chiang Mai district towards KTC Titanium credit card membership privileges. Questionnaires were used as the tool to collect data from the holders of KTC Titanium credit card in Mueang Chiang Mai district. Data obtained were, then, analyzed by the descriptive statistics, including frequency, percentage, and mean. Most respondents were female aged of 26-30 years old and graduated in bachelor’s degree. They worked as a private company employee and earned average monthly income at the amount of 15,001-30,000 Baht. Most of them held the KTC Titanium Master Card with the purpose of purchasing goods and services prior to making payment upon the bill. Type of goods and services that thy purchased via credit card was consumer product. The responses of customers in Mueang Chiang Mai district towards KTC Titanium credit card membership privileges on the reward points redemption for product discount was rated as the highest level of average score according to AIDA Model. In the stage of attention, the respondents learned about the basic information of privileges from the brochure attached to the invoice. They knew about the privilege on the reward points redemption for product discount at collaborative shops. In the stage of interest, the respondents searched for more information from KTC call center and their inquiry included their privilege and how to redeem reward points for cash discount. In the stage of desire or wish towards privileges, the respondents desired to spend the reward points for cash discount. In the stage of action, they used to spend their reward points for product discount at the collaborative shops.